Bio-separator and bio-synthesizer of metallic nanoparticles - A new vision in bioremediation - Salvadori, Marcia Regina; Ando, Rômulo Augusto; Corrêa, Benedito (Materials letters, 2022)
•A bio-separator and biosynthesizer synchronics of NPs from dead cells of the yeast.•Formation of bimetallic systems of NPs: extracellularly and intracellularly.•Bioremediation of bimetallic systems through an environmentally safe technique.•Synthesis of NPs with high aggregate value compared to the raw metal.•Synthesis and separation of Ni/NiO NPs, Ag/Ag2O and Cu NPs. The conception of a bio-separator and bio-synthesizer synchronics of nanoparticles (NPs) from dead cells of the yeast Rhodotorula mucilaginosa (R. mucilaginosa), presents itself as a strong candidate for bioremediation. In this research, the dead yeast cells allowed the synthesis and simultaneous separation of silver, copper and nickel NPs, in aqueous medium, under green physical–chemical conditions. Through the yeast cell wall occurred, the formation of two bimetallic systems of NPs: one of Ni/NiO NPs extracellularly - Ag/Ag2O NPs intracellularly, and another of Ni/NiO NPs extracellularly - Cu NPs intracellularly. This sustainable protocol represents an efficient metals uptake method. Such natural bioprocess is a rational platform for the distinct synthesis of NPs (extra and intracellularly), for possible use in nanobioremediation of sites impacted by multiple toxic metals, being easy to handle, effective cost, and concomitant synthesis of NPs.